2021
DOI: 10.3389/fgene.2021.688292
|View full text |Cite
|
Sign up to set email alerts
|

Using Molecular Transmission Networks to Reveal the Epidemic of Pretreatment HIV-1 Drug Resistance in Guangxi, China

Abstract: IntroductionPretreatment drug resistance (PDR) is becoming an obstacle to the success of ART. This study investigated the prevalence of PDR and the transmission clusters (TCs) of drug resistance mutations (DRMs) in two cities where drug abuse used to be high to describe the local HIV-1 transmission dynamics.MethodsPlasma samples were obtained from 1,027 ART-naïve patients in Guangxi. Viral subtypes and DRMs were identified. Transmission network and related factors were also determined.ResultsA total of 1,025 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…The distribution of HIV-1 genotypes may have changed with the rapid growth of the migrant population and movement of the HIV-1-infected population within China. This could explain why genotype CRF08_BC has now been identified outside of Yunnan province [1,7,8], as well as its apparent increasing trend in our study.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The distribution of HIV-1 genotypes may have changed with the rapid growth of the migrant population and movement of the HIV-1-infected population within China. This could explain why genotype CRF08_BC has now been identified outside of Yunnan province [1,7,8], as well as its apparent increasing trend in our study.…”
Section: Discussionmentioning
confidence: 64%
“…A total of 1110 patients with HIV-1 who met the following inclusion criteria were enrolled in our study: (1) visited Chongqing Public Health Medical Center between January 1, 2018 to June 30, 2021; (2) ART-naïve, which refers to PLWH who had no previous evidence of initiating ART; (3) successfully completed testing for CD4 + T-cell counts, HIV-1 RNA viral load, HIV-1 genotype, and PDR, and all testing reports were traceable. The baseline data of these participants, including demographic information (gender, age, level of education, marital status) and epidemiological information (route of infection, duration between HIV diagnosis and ART initiation) were collected and analyzed anonymously; thus, the usual requirement for written or oral informed consent was waived.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent investigations in Guangxi showed that patients with CRF08_BC were more likely to develop DRM and shared DRM in the transmission network, but there was no significant difference in the prevalence of DRM among different infectious route groups. 37 , 41 These data suggest that it is necessary to modify ART regimens for patients who have a high risk of DRM. PI-based regimens may be more suitable than NNRTI-based regimens for patients with CRF08_BC as the primary regimens.…”
Section: Discussionmentioning
confidence: 99%